Secondary childhood acute myeloid leukemia with complex karyotypic anomalies including monosomy 7, monosomy 5 and translocation (1;10) after 131I-metaiodobenzylguanidine therapy for relapsed neuroblastoma - Incesoy-Ozdemir, Sonay; Bozkurt, Ceyhun; Yüksek, Nazmiye; Oren, Ayşe Ceyda; Sahin, Gürses; Bozkurt, Süreyya; Ertem, Ulya (The Turkish Journal of Pediatrics, 2011)
The prognosis for relapsing or refractory neuroblastoma (NB) remains dismal, with a five-year disease-free survival of < 20%, and no effective salvage treatment has been identified so far. 131I-metaiodobenzylguanidine (131I-MIBG) has come to play an essential role in the imaging and therapy of NB over the past 30 years. The role of 131I-MIBG in the treatment of NB is continually expanding. 131I-MIBG treatment together with cumulative doses of other alkylating agents has potential serious late side effects such as myelodysplasia and leukemia, although rare. We describe a secondary acute myeloid leukemia case with complex karyotypic anomalies that included monosomy 5, monosomy 7 and translocation (1;10) in a child with relapsed NB who received therapeutic 131I-MIBG.